Proposing a framework for blockchain-based implementation in cadastral systems of conflict-impacted communities - Maan Habib; Maan Okayli; Ahed Habib (Discover Computing)
Abstract The effective management of cadastral systems in conflict-impacted communities is fraught with challenges, such as land disputes, insecure land tenure, and pervasive corruption. This study introduces a blockchain-based framework as a potential solution to these challenges, utilizing the technology's inherent strengths in decentralization, security, transparency, and immutability. It comprehensively analyzes the issues afflicting cadastral systems in conflict areas, explores blockchain technology's core principles and capabilities, and investigates its applicability in various aspects of land registry, property rights management, and administrative governance. In addition, the research discusses existing literature, illustrating the implementation of blockchain in cadastral systems and highlighting the observed benefits, such as enhanced efficiency, fraud prevention, and improved stakeholder collaboration. It examines the challenges and limitations associated with blockchain implementation, including technological complexities, legal and regulatory hurdles, and socio-cultural considerations. The study findings reveal future directions, emerging trends, and the importance of strategic collaborations, offering policy recommendations focused on innovation, capacity building, and stakeholder engagement for the successful integration of blockchain in cadastral systems of conflict-impacted communities.